Moderate financial incentive does not appear to influence the P300 Concealed Information Test (CIT) effect in the Complex Trial Protocol (CTP) version of the CIT in a forensic scenario, while affecting P300 peak latencies and behavior - Rosenfeld, J. Peter; Sitar, Evan; Wasserman, Joshua; Ward, Anne (International journal of psychophysiology, 2018)
Previous research indicated that the skin conductance response (SCR) of the Autonomic Nervous System (ANS) in the Concealed Information Test (CIT) is typically increased in subjects who are financially and otherwise incentivized to defeat the CIT (the paradoxical “motivational impairment” effect). This is not the case for RT-based CITs, nor for P300 tests based on the 3-stimulus protocol or Complex Trial Protocol for detection of cognitive malingering (although these are not the same as forensic CITs). The present report extends earlier studies of malingerers by running five groups of subjects (15–16 per group yielding 78 total) in a mock crime (forensic) scenario: paid (to beat the test) and unpaid, instructed and uninstructed, and simply guilty. There was no evidence that the “CIT effect” (probe-minus-irrelevant P300 differences) differed among groups, although behavioral differences among groups were seen. •Previously, no effect of motivation was found in P300-based CIT for malingering.•We now study motivational effects on P300-based CIT for mock crime.•We report clear evidence of motivation on psychological variables.•We saw no effects of motivation on the P300 CIT Effect.